AVERROEISME: AJARAN IBNU RUSYD YANG DIPAHAMI DUNIA BARAT DAN PENGARUHNYA TERHADAP RENAISSANCE - Kosasih, Ade; Muhammad Fahmi, Rezza Fauzi (Jazirah: Jurnal Peradaban dan Kebudayaan, 2024)
The discourse on the role and contribution of Muslim scholars to the progress of mankind and modern life needs great attention. Their traces cannot be erased either from the existing facts or the collective memory of mankind. Ibn Rushd is one of the Muslim scholars who has made his mark on the Western World. Ibn Rushd is known in the Western world as Averroes. It is an indisputable fact that the traces of Ibn Rushd's scholarship are very clear in the Western world. This research explores the teachings and thoughts of Ibn Rushd who were influential in the Western World. The result of Ibn Rushd's thought has a very strong network to this day. The various rationality movements that took place in the West were inspired by the thought of Ibn Rushd. Therefore, the expression of Ibn Rushd's thought is something that really needs to be revealed, both its origin and its substance. The revelation of the origins and substance of this thought will prove the extent to which Muslim scholars contributed to modern civilization. Ibn Rushd's thought related to the relationship between philosophy and religion, namely that between philosophy and religion are interrelated. Philosophy reveals the nature of truth based on ratios; while Islam expresses a truth based on revelation from God. Islamic philosophy and religion should not contradict, so that the two cannot be separated and should even strengthen each other. Ibn Rushd's thought is understood and implemented by the West very differently, that is, only philosophical thought is considered correct.